Enhancing farm income in Island ecosystem - Ravishankar, N; Subramani, T; Ambast, S K; Srivastava, R C (Indian Farming, 2015)
Net returns from various systems and technologies identified are ranging from Rs 13,257 to Rs 164,960/ha over the traditional practice of monoculture of paddy with ‘C 14-8’ variety. Improved highyielding long duration variety of paddy followed by table-purpose groundnut can lead to return of Rs 72,000/ha. In the case of double cropping of paddy, the return from investment is lesser compared to monocrop of paddy with improved high-yielding late duration varieties. Through promotion of integrated farming system (IFS) in low lying valley areas, the farm income can be raised to as high as Rs 164,960/ha, but the return from investment is lesser compared to broad bed and furrow system in which around Rs 117,532/ha can be obtained with as high as B:C ratio of 2.95.